Adsorbent
By combining adsorbent A and B with specific particle sizes and fixation ratios, the filter addresses structural irregularities and pressure loss issues, achieving efficient pollutant removal with low pressure loss.
Patent Information
- Application Number
- JP2023107689
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-30
- Publication Date
- 2025-01-17
AI Technical Summary
Existing filters for removing volatile organic compounds suffer from high pressure loss due to structural irregularities and particle size issues, leading to inconsistent performance.
The use of adsorbent A with an average particle length of 200 μm to 1000 μm and adsorbent B with an average particle length of 0.1 μm to 100 μm, where adsorbent B is fixed to the surface of adsorbent A in a specific ratio, creating a structure that maintains high removal efficiency while minimizing pressure loss.
The adsorbent combination achieves high pollutant removal rates with low pressure loss, forming an adsorption filter that effectively captures volatile organic compounds like toluene and acetaldehyde.
Smart Images

Figure 2025006714000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an adsorbent for removing contaminants. [Background technology]
[0002] In recent years, as one of the measures to deal with environmental problems, interest in measures against odor pollution has been growing. For example, odor pollution is pollution caused by exhaust gas. Among exhaust gases, volatile organic compounds such as toluene and acetaldehyde are considered to be causative substances of sick house syndrome, and the removal and deodorization of these odorous substances is a major issue. It is known that these exhaust gases can be removed by filters attached to air purification devices such as air purifiers and air conditioners. It is preferable that this filter has low pressure loss, i.e., high breathability.
[0003] There is a high demand for a filter that has high pollutant removal performance and low pressure loss as a filter for removing the above-mentioned pollutants. In response to this demand, for example, in Patent Document 1, activated carbon particles of the same particle diameter are bonded and aggregated with a thermoplastic resin to form irregular aggregates, thereby creating voids between the aggregates, thereby realizing low pressure loss. In addition, in Patent Document 2, particles with an average particle diameter of 1 μm or less are supported on a nonwoven fabric, thereby achieving high volatile organic compound removal performance. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent No. 3612329 [Patent Document 2] JP 2015-157250 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, the filter of Patent Document 1 has problems such as the aggregates collapsing due to the external force applied when forming the adsorbent into a sheet, filling the voids and increasing the pressure loss, and the irregular structure of the formed aggregates results in a large variation in performance. Also, the filter of Patent Document 2 has problems such as the particle diameter of the particles used being small, and the adsorbent particles filling the voids between the nonwoven fibers, increasing the pressure loss.
[0006] In view of the above circumstances, an object of the present invention is to provide an adsorbent that has high removal performance for pollutants including volatile organic compounds, and that, when used to prepare an adsorption filter, can produce an adsorption filter with low pressure loss. [Means for solving the problem]
[0007] The adsorbent according to the embodiment of the present invention that can solve the above problems is as follows. [1] An adsorbent A having an average particle length of 200 μm to 1000 μm and an adsorbent B having an average particle length of 0.1 μm to 100 μm, The adsorbent B is fixed to the surface of the adsorbent A, The number of the adsorbents B fixed to each particle of the adsorbent A is 500 or more.
[0008] The above adsorbent contains adsorbent B, which has a small average particle major axis of 0.1 μm to 100 μm, so that the surface area for adsorbing pollutants can be increased, and the removal rate of pollutants can be increased. In addition, since 500 or more particles of adsorbent B, which has a small average particle major axis, are fixed to the surface of adsorbent A, which has a large average particle major axis of 200 μm to 1000 μm, an adsorption filter with low pressure loss can be obtained when the above adsorbent is used to produce an adsorption filter.
[0009] The adsorbent according to the embodiment of the present invention is preferably any one of the following [2] to [7]. [2] Average particle length R of the adsorbent A A and the average particle length R of the adsorbent B BRatio of R B / R A The adsorbent according to [1], wherein the molecular weight is 1 / 5000 to 1 / 5. [3] Average particle length R of the adsorbent A A , the average particle major axis R of the adsorbent B B , and the weight ratio P ((weight of adsorbent A) / (weight of adsorbent B)) of the adsorbent A and the adsorbent B is P=R A 3 / [{(R A +2R B ) 3 -R A 3}×X], where X is 0.1 or more and 10 or less. [4] The adsorbent according to any one of [1] to [3], wherein the adsorbent A is any one of activated carbon, activated alumina, silica gel, and zeolite. [5] The adsorbent according to any one of [1] to [4], wherein the adsorbent B is any one of activated carbon, activated alumina, silica gel, and zeolite. [6] The adsorbent according to any one of [1] to [5], wherein the adsorbent B is fixed to the surface of the adsorbent A via a binder. [7] The adsorbent according to [6], wherein the binder is at least one selected from the group consisting of sodium alginate, polyvinyl alcohol, polyacrylamide, carboxymethyl cellulose, polyvinylpyrrolidone, polyacrylic acid, polymethacrylic acid, polystyrene sulfonic acid, polyethylene glycol, polypropylene glycol, polyvinyl acetate, and copolymers thereof. Effect of the Invention
[0010] The above-mentioned adsorbent has an improved ability to remove pollutants such as volatile organic compounds, and when used to prepare an adsorption filter, the adsorption filter has a low pressure loss. [Brief description of the drawings]
[0011] [Figure 1] 1 is a scanning electron microscope photograph of the adsorbent obtained in Example 2. [Diagram 2] 1 is a graph showing the relationship between the toluene removal rate and the pressure loss when the adsorption filters were made using the adsorbents of Examples 1 to 16 and Comparative Examples 1 to 5. [Diagram 3] 1 is a graph showing the relationship between the toluene removal rate and the pressure loss when the adsorption filters were made using the adsorbents of Example 17 and Comparative Example 6. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, the present invention will be described based on the embodiments. However, the present invention is not limited to the following embodiments, and can be modified as appropriate within the scope of the above and below described spirit, and all of these are included in the technical scope of the present invention.
[0013] The adsorbent according to the embodiment of the present invention includes adsorbent A having an average particle major axis of 200 μm to 1000 μm and adsorbent B having an average particle major axis of 0.1 μm to 100 μm, adsorbent B being fixed to the surface of adsorbent A, and the number of particles of adsorbent B fixed to each particle of adsorbent A being 500 or more. Thus, the adsorbent according to the embodiment of the present invention includes adsorbent A and adsorbent B, but in order to avoid confusion with adsorbent A and adsorbent B, the adsorbent according to the embodiment of the present invention will be hereinafter referred to as "adsorbent C."
[0014] Adsorption occurs at the interface between the gas phase, liquid phase, or solid phase and the adsorbent, so that the adsorbed substance can be adsorbed to the adsorbent with high efficiency by increasing the contact probability at the interface between the adsorbent and the adsorbed substance. The adsorbent C according to the embodiment of the present invention contains the adsorbent B having a small average particle major axis of 0.1 μm to 100 μm, and therefore has a large surface area per unit volume, and can have a high removal rate of pollutants. In addition, when the adsorbent C is made into a sheet to be used as an adsorption filter, if the particle diameter of the particles contained in the adsorbent C is small, the voids are filled and the packing density becomes high, resulting in high pressure loss. In this regard, in the adsorbent C according to the embodiment of the present invention, 500 or more particles of the adsorbent B having a small average particle major axis are fixed to the surface of the adsorbent A having a large average particle major axis of 200 μm to 1000 μm. As a result, when an adsorption filter is produced using the adsorbent C, voids are easily formed between the particles, so that the packing density does not become too high, and an adsorption filter having low pressure loss can be obtained.
[0015] When producing the adsorbent C, the adsorbent A having an average particle major axis of 200 μm to 1000 μm and the adsorbent B having an average particle major axis of 0.1 μm to 100 μm can be obtained by sieving the adsorbent particles through a mesh. The mesh size can be selected according to the major axis of the particles to be obtained, for example, the adsorbent A having a large average particle major axis is obtained by removing particles that can pass through a mesh of No. 18 but cannot pass through a mesh of No. 65 or more, and the adsorbent B having a small average particle major axis is obtained by sieving through a mesh of No. 160 or more.
[0016] After being produced as adsorbent C, the major axis of adsorbent A and adsorbent B contained in adsorbent C can be measured from a micrograph such as a scanning electron microscope (SEM). The major axis of adsorbent A and adsorbent B can be determined by, for example, observing 100 pieces of adsorbent A and adsorbent B with an SEM, measuring the length of the longest line segment among the lines connecting the outer edges of one particle, and averaging the measured values of the 100 pieces. In the micrograph, if the shape of the particle is circular, the length of the line segment is the diameter of the circle, if the shape of the particle is elliptical, the length of the line segment is the major axis of the ellipse, and if the shape of the particle is rectangular, the length of the line segment is the length of the diagonal of the rectangle, but the shape of the particle is not limited to the above shapes. Whatever the shape of the particle, the major axis can be uniquely determined by the above definition.
[0017] The average particle major axis of the adsorbent A is 200 μm or more, preferably 250 μm or more, more preferably 300 μm or more, even more preferably 350 μm or more, particularly preferably 375 μm or more, and may be 400 μm or more. If the lower limit of the average particle major axis of the adsorbent A is within the above range, the pressure loss when an adsorption filter is produced using the adsorbent C can be reduced. In addition, the average particle major axis of the adsorbent A is 1000 μm or less, preferably 900 μm or less, more preferably 850 μm or less, even more preferably 800 μm or less, and may be 750 μm or less. If the upper limit of the average particle major axis of the adsorbent A is within the above range, there is an advantage that when the adsorbent C is made into a sheet to produce an adsorption filter, the thickness does not become too thick and production is facilitated.
[0018] The average particle major axis of the adsorbent B is 0.1 μm or more, preferably 0.5 μm or more, more preferably 1 μm or more, and even more preferably 5 μm or more. If the lower limit of the average particle major axis of the adsorbent B is within the above range, the cohesive force of the adsorbent B is not too strong, and the adsorbent B can be uniformly fixed to the surface of the adsorbent A. In addition, the average particle major axis of the adsorbent B is 100 μm or less, preferably 75 μm or less, more preferably 50 μm or less, and even more preferably 30 μm or less. If the upper limit of the average particle major axis of the adsorbent B is within the above range, the adsorption force of the adsorbent B to the surface of the adsorbent A can be secured, and it is easy to prevent the adsorbent B from falling off from the adsorbent A. By having the average particle major axis of the adsorbent B within the above range, it is possible to uniformly and strongly adhere the adsorbent B to the surface of the adsorbent A.
[0019] The number of adsorbents B adhering to each adsorbent A is 500 or more, preferably 600 or more, more preferably 800 or more, even more preferably 1,000 or more, and particularly preferably 2,000 or more. If the lower limit of the number of adsorbents B adhering to each adsorbent A is within the above range, the contaminant removal rate of the adsorbent C can be improved by the adsorbent B. The upper limit of the number of adsorbents B adhering to each adsorbent A is not particularly limited, but may be, for example, 2,000,000 or less, more preferably 1,000,000 or less, more preferably 500,000 or less, particularly preferably 100,000 or less, 80,000 or less, 50,000 or less, 30,000 or less, 10,000 or less, 9,000 or less, or 8,000 or less. The number of particles of adsorbent B that can be attached to the surface of adsorbent A depends on the size of adsorbent B relative to the surface area of adsorbent A. However, if the upper limit of the number of particles of adsorbent B attached to each particle of adsorbent A is within the above-mentioned range, adsorbent B is less likely to fall off the surface of adsorbent A, and the pressure loss can be reduced when an adsorption filter is produced using adsorbent C.
[0020] The number of adsorbents B adhering to each particle of adsorbent A can be obtained from a micrograph taken with a scanning electron microscope (SEM) or the like. The number of adsorbents B adhering to each particle of adsorbent A can be obtained, for example, by observing 10 particles of adsorbent C with an SEM, counting the number of particles of adsorbents B adhering to the surface of adsorbent A in each of the particles of adsorbent C, and then doubling this number assuming that the same number of particles of adsorbents B are adhering to the surface opposite to the observation surface, and averaging the measured values obtained for the 10 particles.
[0021] Average particle length R of adsorbent A A and the average particle length R of the adsorbent B B Ratio of R B / R A The ratio R is preferably 1 / 5000 to 1 / 5, more preferably 1 / 1000 to 1 / 10, further preferably 1 / 500 to 1 / 20, and most preferably 1 / 100 to 1 / 30. B / R A By setting the ratio R to 1 / 5000 or more, the cohesive force of adsorbent B is not too strong, and adsorbent B can be uniformly fixed to the surface of adsorbent A. B / R A By making the size of adsorbent B relative to the surface area of adsorbent A be 1 / 5 or less, the size of adsorbent B relative to the surface area of adsorbent A does not become too large, making it easier to ensure the adhesive force of adsorbent B to the surface of adsorbent A and preventing adsorbent B from falling off from adsorbent A.
[0022] Average particle length R of adsorbent A A , the average particle major axis R of the adsorbent B B and the weight ratio P of the adsorbent A to the adsorbent B ((weight of adsorbent A) / (weight of adsorbent B)) preferably satisfies the relationship of the following formula (1). P=R A 3 / [{(R A +2R B ) 3 -R A 3}×X] ···(1)
[0023] Equation (1) indicates that the weight ratio P ((weight of adsorbent A) / (weight of adsorbent B)) corresponds to (volume of adsorbent A) / (volume of adsorbent B). Here, the volume of adsorbent A is approximately R A 3 In addition, in the case of adsorbent C, adsorbent B is fixed to both sides of adsorbent A, and the major axis R of adsorbent A is A The major axis R of adsorbent B is B Add twice the volume of the adsorbent C and cube it to find the volume (R A +2R B ) 3 From this, the volume of adsorbent A, R A 3 By subtracting A +2R B ) 3 -R A 3 The smaller X is, the smaller the amount of adsorbent B adhering to the surface of adsorbent A is, and the larger X is, the larger the amount of adsorbent B adhering to the surface of adsorbent A is.
[0024] X is preferably 0.1 to 10, more preferably 0.2 to 8.0, even more preferably 0.4 to 5.0, and most preferably 0.5 to 2.0. If X is within this range, it is easy to obtain adsorbent C in which adsorbent B is uniformly fixed to the surface of adsorbent A. If X is less than 0.1, the amount of adsorbent B is too small, making it difficult to obtain the effects of the present invention. In addition, if X is greater than 10, it is considered that multiple layers of adsorbent B are deposited on the surface of adsorbent A, and even if the amount of adsorbent B is increased so that X is greater than 10, it is unlikely that the effect of reducing the pressure loss of the adsorption filter will be improved compared to when X is 0.1 to 10. Conversely, if X is too large, adsorbent B will be easily detached from the surface of adsorbent A, which is considered to increase the pressure loss of the adsorption filter. From this viewpoint, X is preferably 15 or less, more preferably 12 or less.
[0025] Adsorbent A and adsorbent B are preferably made of a material capable of capturing ions or molecules of contaminants, such as toluene or acetaldehyde, contained in the gas phase, thereby removing them from the gas phase.
[0026] The adsorbent A is not particularly limited as long as it is the above-mentioned material, but is preferably any one of activated carbon, activated alumina, silica gel, and zeolite. These may be used alone or in combination of two or more. To remove volatile organic compounds such as toluene and aldehydes, the adsorbent A is preferably composed of activated carbon or silica gel.
[0027] The adsorbent B is not particularly limited as long as it is the above-mentioned material, but is preferably any one of activated carbon, activated alumina, silica gel, and zeolite. These may be used alone or in combination of two or more. To remove volatile organic compounds such as toluene and aldehydes, the adsorbent B is preferably composed of activated carbon or silica gel.
[0028] The material constituting adsorbent A and the material constituting adsorbent B may be the same or different, but are preferably the same, which can ensure the adhesive force of adsorbent B to the surface of adsorbent A.
[0029] The activated carbon is not particularly limited, but it is preferable to use common activated carbon such as coconut shell activated carbon, coal-based activated carbon, wood-based activated carbon, and synthetic resin-based activated carbon in terms of performance and availability.
[0030] The BET specific surface area of the activated carbon is not particularly limited, but is preferably 800 m 2 / g~1500m 2 / g is preferred, and 850m 2 / g~1300m 2 / g is more preferable. 2 / g or more, it is easy to obtain a deodorizing effect. In addition, the BET specific surface area of the activated carbon is 1500 m2 / g or less, it is possible to prevent contaminants that have been adsorbed from being desorbed.
[0031] The pore volume of the activated carbon is not particularly limited, but is preferably 0.30 cm 3 / g~0.70cm 3 / g is preferred, and 0.40 cm 3 / g~0.55cm 3 / g is more preferable. 3 / g or more, the deodorizing effect is easily obtained. 3 / g or less, it is possible to prevent contaminants that have been adsorbed from being desorbed.
[0032] The average pore diameter of the activated carbon can be appropriately adjusted depending on the object to be adsorbed. For example, when the object to be adsorbed is toluene, the average pore diameter is preferably 15 Å to 19 Å, and more preferably 16 Å to 18 Å.
[0033] The BET specific surface area of the silica gel is not particularly limited, but is preferably 20 m 2 / g~1000m 2 / g is preferred, 50m 2 / g~700m 2 / g is more preferable. The BET specific surface area of the silica gel is 20 m 2 / g or more, the deodorizing effect is easily obtained. In addition, the BET specific surface area of the silica gel is 1000 m 2 / g or less, it is possible to prevent contaminants that have been adsorbed from being desorbed.
[0034] It is preferable that the adsorbent B is fixed to the surface of the adsorbent A via a binder. This makes it easy for the adsorbent B to be fixed to the surface of the adsorbent A, and makes it easy to prevent the adsorbent B from falling off the surface of the adsorbent A. As a result, when the adsorbent C is formed into a sheet to form an adsorption filter, it is possible to prevent the adsorbent B that has fallen off the surface of the adsorbent A from filling the voids formed by the adsorbent A, which has a large average particle major axis, resulting in an increase in pressure loss.
[0035] The binder is not particularly limited as long as it can fix the adsorbent B to the surface of the adsorbent A, and examples thereof include water-soluble polymers, thermoplastic resins, and water-dispersible polymers. In particular, the binder is preferably a water-soluble polymer. The water-soluble polymer preferably has a solubility in water of 1 g or more at 20° C. and 1 atm, and a molecular weight of 10,000 or more. The binder is preferably a water-soluble polymer, and is preferably at least one selected from the group consisting of sodium alginate, polyvinyl alcohol, polyacrylamide, carboxymethyl cellulose, polyvinylpyrrolidone, polyacrylic acid, polymethacrylic acid, polystyrene sulfonic acid, polyethylene glycol, polypropylene glycol, polyvinyl acetate, and copolymers thereof.
[0036] By using a water-soluble polymer as the binder, adsorbent B can be easily fixed to the surface of adsorbent A even if only a small amount of binder is added.
[0037] The binder solution concentration is preferably 0.1% by weight to 10% by weight, and more preferably 1% by weight to 5% by weight. By setting the binder solution concentration to 0.1% by weight or more, the adhesive force of adsorbent B to the surface of adsorbent A can be ensured. By setting the binder solution concentration to 10% by weight or less, the problem of the binder coating the adsorbent particles, which occurs when the binder solution concentration exceeds 10% by weight, can be avoided. The binder solution concentration may be the solution concentration of the water-soluble polymer.
[0038] The method for producing adsorbent C is not particularly limited, but examples thereof include a method in which adsorbent A and adsorbent B are immersed in an aqueous solution in which a water-soluble polymer is dissolved, followed by stirring and then drying, and a method in which an aqueous solution in which a water-soluble polymer is dissolved is made into a mist or mist form and sprayed onto adsorbent A and adsorbent B, followed by drying.
[0039] The adsorbent C is a material intended to remove ions or molecules contained in a gas phase, such as toluene or acetaldehyde, from the target gas phase by capturing them therein, and can be used for various purposes. Although not particularly limited, the adsorbent C can be used, for example, in a filter attached to an air purification device such as an air purifier or an air conditioner.
[0040] The filter manufactured using the adsorbent C can be obtained by molding the filter material. The molding method is not particularly limited, but the method of processing the filter material into a flat, pleated, or honeycomb shape is preferable. The pleated shape can be used as a cross-flow type filter, and the honeycomb shape can be used as a flat flow type filter, and can increase the contact area with the gas to be treated, improve the removal rate of pollutants, and simultaneously reduce the pressure loss of the filter.
[0041] The above filter medium can be obtained by processing the adsorbent C into a sheet. The method of forming the sheet is not particularly limited and can be a known processing method. For example, (a) a wet sheeting method obtained by dispersing the adsorbent C in water together with the sheet-constituting fibers and dehydrating it, (b) an air-laid method obtained by dispersing the adsorbent C in air together with the sheet-constituting fibers, (c) a method of filling the adsorbent C between layers of two or more layers of nonwoven fabric, woven fabric, net-like material, film, membrane, etc. by thermal adhesion, (d) a method of bonding and supporting the adsorbent C on a breathable material such as a nonwoven fabric, woven fabric, or urethane foam using an emulsion adhesive or a solvent-based adhesive, (e) a method of supporting the adsorbent C on a breathable material such as a nonwoven fabric, woven fabric, or urethane foam using the thermoplasticity of a thermoplastic resin, (f) a method of mixing and integrating the adsorbent C by kneading it into fibers or resin, etc., can be used according to the application. In particular, it is preferable to use the processing methods (b), (c), and (e) among the above processing methods, since it is not necessary to use a surfactant and it is possible to prevent the adsorbent from being covered by the surfactant.
[0042] The adsorbent C according to the embodiment of the present invention and a filter manufactured using the same can be used indoors, in vehicles, etc., and is preferably used for the purpose of removing volatile organic compounds such as toluene and aldehyde in wallpaper, furniture, interior materials, resin molded bodies, electrical equipment, etc. In addition, the adsorbent C is preferably filled in a breathable container such as a box, bag, or net, and left to stand or ventilate before use. EXAMPLES
[0043] The present invention will be described below with reference to examples. The present invention is not limited to the examples, and any design modifications made in accordance with the spirit described above and below are included within the technical scope of the present invention.
[0044] (Number of adsorbents B adhering to adsorbent A) Ten pieces of each of the adsorbents obtained in each of the Examples and Comparative Examples were observed under a scanning electron microscope (SEM). From the SEM observation photographs, the number of pieces of adsorbent B adhering to the surface of each piece of adsorbent A was counted. Assuming that the same number of pieces of adsorbent B were adhering to the side opposite to the observation side, this number was doubled, and the average of the obtained 10 measurements was taken as the number of pieces of adsorbent B adhering to adsorbent A. In this case, the tens digit was rounded off.
[0045] (Measurement of toluene removal rate) Cross-sectional area 36cm 2 A sheet of adsorbent was sandwiched between the two columns. Air with a toluene vapor concentration of 80 ppm was supplied to the column at a linear velocity of 20 cm / sec, a temperature of 25°C, and a humidity of 50% RH. The toluene concentration at the column outlet was measured after 1 minute, and the removal rate (η) was calculated using the following formula (2). In the following formula (2), Ci (ppm) is the toluene concentration at the inlet, and Co (ppm) is the toluene concentration at the outlet. The toluene concentration was measured using a hydrocarbon system. Removal rate η(%)=[1-(Co / Ci)]×100 ···(2)
[0046] (Pressure loss measurement) The sheet-formed adsorbent was placed inside a duct, and the linear velocity passing through the sheet was controlled to be 10.4 cm / sec. The pressure drop (mmaq) was calculated by reading the static pressure difference upstream and downstream of the sheet with a pressure gauge.
[0047] <Example 1> Adsorbent A was granular activated carbon (average particle diameter 300 μm, specific surface area 1000 m 2 / g, pore volume 0.46 cm 3 / g, average pore size 17 Å) and powdered activated carbon (average particle length 15 μm, specific surface area 1000 m) as adsorbent B. 2 / g, pore volume 0.46 cm 3 Activated carbon powder and granular activated carbon (17Å / g, average pore size 17Å) were mixed in a weight ratio of 3:1, and an aqueous solution of sodium alginate (ALG-Na) was added in an amount of 0.46 times the total weight of the granular activated carbon and powdered activated carbon and mixed. The molecular weight of sodium alginate (ALG-Na) was 55,000, and the concentration of the aqueous solution of sodium alginate (ALG-Na) was 4.4% by weight. This was dried to obtain an adsorbent in which powdered activated carbon was fixed to the surface of the granular activated carbon. The obtained adsorbent was observed with an SEM, and the number of adsorbent B fixed to adsorbent A was determined from the SEM photographs using the method described above.
[0048] The adsorbent obtained in Example 1 was made into a sheet to produce an adsorption filter. The downstream layer was a thermal bond nonwoven fabric, and the adsorbent obtained in Example 1 was mixed with a thermoplastic powder resin as an adhesive in a weight ratio of 20:1 to produce a filter with a basis weight of 200 g / m. 2 The adsorption filter was obtained by heating an electret nonwoven fabric as the upstream layer and carrying the adsorbent on the nonwoven fabric. The toluene removal rate and pressure loss of this adsorption filter were measured by the above-mentioned method. The manufacturing conditions of the adsorbent and the measurement results are shown in Table 1.
[0049] <Comparative Example 1> Granular activated carbon (average particle diameter 300 μm, specific surface area 1000 m 2 / g, pore volume 0.46 cm 3The adsorption filter was fabricated by forming a sheet of a thermobond nonwoven fabric as the downstream layer, and the above adsorbent and a thermoplastic powder resin as an adhesive were mixed in a weight ratio of 20:1 to form a sheet with a basis weight of 200 g / m2. 2 The adsorption filter was obtained by heating an electret nonwoven fabric as the upstream layer and carrying the adsorbent on the nonwoven fabric. The toluene removal rate and pressure loss of this adsorption filter were measured by the above-mentioned method. The manufacturing conditions of the adsorbent and the measurement results are shown in Table 1.
[0050] [Table 1]
[0051] In Example 1 and Comparative Example 1, the pressure loss was equivalent because the average particle length of the granular activated carbon used was the same. However, since adsorbent B was not used in Comparative Example 1, the toluene removal rate was lower than that of Example 1.
[0052] <Example 2> Adsorbent A was granular activated carbon (average particle diameter 600 μm, specific surface area 1000 m 2 / g, pore volume 0.46 cm 3 / g, average pore size 17 Å) and powdered activated carbon (average particle length 15 μm, specific surface area 1000 m) as adsorbent B. 2 / g, pore volume 0.46 cm 3 Activated carbon powder and granular activated carbon (17Å / g, average pore size) were mixed in a weight ratio of 7:1, and an aqueous solution of sodium alginate (ALG-Na) was added in an amount of 0.46 times the total weight of the granular activated carbon and powdered activated carbon and mixed. The molecular weight of sodium alginate (ALG-Na) was 55,000, and the concentration of the aqueous solution of sodium alginate (ALG-Na) was 4.4% by weight. This was dried to obtain an adsorbent in which powdered activated carbon was fixed to the surface of the granular activated carbon. An SEM photograph of the obtained adsorbent is shown in Figure 1. Using the above method, the number of adsorbents B fixed to adsorbent A was determined from the SEM photograph.
[0053] The adsorbent obtained in Example 2 was made into a sheet to produce an adsorption filter. The downstream layer was a thermal bond nonwoven fabric, and the adsorbent obtained in Example 2 was mixed with a thermoplastic powder resin as an adhesive in a weight ratio of 20:1 to produce a filter with a basis weight of 200 g / m. 2 The adsorption filter was obtained by heating an electret nonwoven fabric as the upstream layer and carrying the adsorbent on the nonwoven fabric. The toluene removal rate and pressure loss of this adsorption filter were measured by the above-mentioned method. The manufacturing conditions of the adsorbent and the measurement results are shown in Table 2.
[0054] <Example 3> An adsorbent was obtained in the same manner as in Example 2, except that the weight ratio of adsorbent A to adsorbent B was changed to 50:1. An adsorption filter was also produced using the obtained adsorbent in the same manner as in Example 2. The manufacturing conditions and measurement results of the adsorbent are shown in Table 2.
[0055] <Example 4> An adsorbent was obtained in the same manner as in Example 2, except that the weight ratio of adsorbent A to adsorbent B was changed to 1:1. An adsorption filter was also produced using the obtained adsorbent in the same manner as in Example 2. The manufacturing conditions and measurement results of the adsorbent are shown in Table 2.
[0056] <Example 5> An adsorbent was obtained in the same manner as in Example 2, except that the weight ratio of adsorbent 1 to adsorbent B was changed to 1:2. An adsorption filter was also produced using the obtained adsorbent in the same manner as in Example 2. The manufacturing conditions and measurement results of the adsorbent are shown in Table 2.
[0057] <Example 6> An adsorbent was obtained in the same manner as in Example 2, except that the concentration of the aqueous sodium alginate (ALG-Na) solution mixed with the granular activated carbon and powdered activated carbon was changed to 9.0% by weight. An adsorption filter was also produced using the obtained adsorbent in the same manner as in Example 2. The manufacturing conditions and measurement results of the adsorbent are shown in Table 2.
[0058] <Example 7> An adsorbent was obtained in the same manner as in Example 2, except that the concentration of the aqueous sodium alginate (ALG-Na) solution mixed with the granular activated carbon and powdered activated carbon was changed to 2.0% by weight. An adsorption filter was also produced using the obtained adsorbent in the same manner as in Example 2. The manufacturing conditions and measurement results of the adsorbent are shown in Table 2.
[0059] <Example 8> An adsorbent was obtained in the same manner as in Example 2, except that the molecular weight of sodium alginate (ALG-Na) mixed with the granular activated carbon and powdered activated carbon was changed to 80,000. An adsorption filter was also produced using the obtained adsorbent in the same manner as in Example 2. The manufacturing conditions and measurement results of the adsorbent are shown in Table 2.
[0060] <Example 9> An adsorbent was obtained in the same manner as in Example 2, except that the molecular weight of sodium alginate (ALG-Na) mixed with the granular activated carbon and powdered activated carbon was changed to 100,000. An adsorption filter was also produced using the obtained adsorbent in the same manner as in Example 2. The manufacturing conditions and measurement results of the adsorbent are shown in Table 2.
[0061] <Example 10> An adsorbent was obtained in the same manner as in Example 2, except that the granular activated carbon and the powdered activated carbon were mixed with a 4.4% by weight aqueous solution of polyvinyl alcohol (PVA) instead of the aqueous solution of sodium alginate (ALG-Na). The molecular weight of the polyvinyl alcohol (PVA) was 90,000. In addition, an adsorption filter was produced using the obtained adsorbent in the same manner as in Example 2. The manufacturing conditions and measurement results of the adsorbent are shown in Table 2.
[0062] <Example 11> An adsorbent was obtained in the same manner as in Example 2, except that a 4.4 wt% aqueous polyacrylamide (PAM) solution was mixed with the granular activated carbon and powdered activated carbon instead of the aqueous sodium alginate (ALG-Na) solution. An adsorption filter was also produced using the obtained adsorbent in the same manner as in Example 2. The manufacturing conditions and measurement results of the adsorbent are shown in Table 2.
[0063] <Example 12> An adsorbent was obtained in the same manner as in Example 2, except that the granular activated carbon and the powdered activated carbon were mixed with a 4.4 wt% aqueous solution of carboxymethylcellulose (CMC) instead of the aqueous solution of sodium alginate (ALG-Na). The molecular weight of the carboxymethylcellulose (CMC) was 120,000. An adsorption filter was also produced using the obtained adsorbent in the same manner as in Example 2. The manufacturing conditions and measurement results of the adsorbent are shown in Table 2.
[0064] <Example 13> An adsorbent was obtained in the same manner as in Example 2, except that the granular activated carbon and the powdered activated carbon were mixed with a 4.4% by weight aqueous solution of polyvinylpyrrolidone (PVP) instead of the aqueous solution of sodium alginate (ALG-Na). The molecular weight of polyvinylpyrrolidone (PVP) was 360,000. An adsorption filter was also produced using the obtained adsorbent in the same manner as in Example 2. The manufacturing conditions and measurement results of the adsorbent are shown in Table 2.
[0065] <Example 14> Adsorbent A was granular activated carbon (average particle diameter 900 μm, specific surface area 1000 m 2 / g, pore volume 0.46 cm 3 An adsorbent was obtained in the same manner as in Example 2, except that adsorbent A and adsorbent B were mixed in a weight ratio of 10:1 using a cellulose acetate ester (cellulose acetate ester, ...
[0066] <Example 15> Adsorbent B was powdered activated carbon (average particle length 50 μm, specific surface area 1000 m 2 / g, pore volume 0.46 cm 3 An adsorbent was obtained in the same manner as in Example 2, except that adsorbent A and adsorbent B were mixed in a weight ratio of 2:1 using 1000 g / g (average pore size 17 Å). An adsorbent filter was produced using the obtained adsorbent in the same manner as in Example 2. The production conditions and measurement results of the adsorbent are shown in Table 2.
[0067] <Example 16> Adsorbent B was powdered activated carbon (average particle length 1 μm, specific surface area 1000 m 2 / g, pore volume 0.46 cm 3 An adsorbent was obtained in the same manner as in Example 2, except that adsorbent A and adsorbent B (wt. / g, average pore size 17 Å) were used and adsorbent A and adsorbent B were mixed in a weight ratio of 100:1. An adsorption filter was produced using the obtained adsorbent in the same manner as in Example 2. The production conditions and measurement results of the adsorbent are shown in Table 2.
[0068] [Table 2]
[0069] <Comparative Example 2> Granular activated carbon (average particle diameter 600 μm, specific surface area 1000 m 2 / g, pore volume 0.46 cm 3 The adsorption filter was fabricated by forming a sheet of a thermobond nonwoven fabric as the downstream layer, and the above adsorbent and a thermoplastic powder resin as an adhesive were mixed in a weight ratio of 20:1 to form a sheet with a basis weight of 200 g / m2. 2 The adsorption filter was obtained by heating an electret nonwoven fabric as the upstream layer and carrying the adsorbent on the nonwoven fabric. The toluene removal rate and pressure loss of this adsorption filter were measured by the above-mentioned method. The manufacturing conditions of the adsorbent and the measurement results are shown in Table 3.
[0070] <Comparative Example 3> Granular activated carbon (average particle diameter 900 μm, specific surface area 1000 m 2 / g, pore volume 0.46 cm 3 An adsorption filter was obtained in the same manner as in Comparative Example 2, except that an adsorbent having a molecular weight of 1.001 g / g and an average pore diameter of 17 Å was used as the adsorbent. The manufacturing conditions and measurement results of the adsorbent are shown in Table 3.
[0071] <Comparative Example 4> An adsorbent was obtained in the same manner as in Example 2, except that the weight ratio of adsorbent A to adsorbent B was changed to 200:1. The number of adsorbent B adhering to adsorbent A was determined from SEM photographs using the above method. In addition, an adsorption filter was produced using the obtained adsorbent in the same manner as in Example 2. The manufacturing conditions and measurement results of the adsorbent are shown in Table 3.
[0072] <Comparative Example 5> Granular activated carbon (average particle diameter 150 μm, specific surface area 1000 m 2 / g, pore volume 0.46 cm 3 The adsorption filter was fabricated by forming a sheet of a thermobond nonwoven fabric as the downstream layer, and the above adsorbent and a thermoplastic powder resin as an adhesive were mixed in a weight ratio of 20:1 to form a sheet with a basis weight of 200 g / m2. 2 The adsorption filter was obtained by heating an electret nonwoven fabric as the upstream layer and carrying the adsorbent on the nonwoven fabric. The toluene removal rate and pressure loss of this adsorption filter were measured by the above-mentioned method. The manufacturing conditions of the adsorbent and the measurement results are shown in Table 3.
[0073] [Table 3]
[0074] As can be seen from Table 2, the adsorbents of Examples 2 to 16 had a high toluene removal rate, and the pressure loss when the adsorbents were used to form an adsorption filter was kept low.
[0075] In contrast, as can be seen from Table 3, in Comparative Examples 2 and 3 in which adsorbent B was not used, the toluene removal rate was low. In Comparative Example 4 in which adsorbent B was used but the weight ratio of adsorbent A to adsorbent B was 200:1, the toluene removal rate was low due to the small amount of adsorbent B. In Comparative Example 5 in which activated carbon having an average particle major axis of 150 μm, which does not correspond to adsorbent A or adsorbent B, was used alone, the toluene removal rate was high, but the pressure loss when used as an adsorption filter was high.
[0076] Fig. 2 shows a graph illustrating the relationship between the toluene removal rate and pressure loss when the adsorption filters were made using the adsorbents of Examples 1 to 16 and Comparative Examples 1 to 5. The horizontal axis represents pressure loss (mmaq) and the vertical axis represents the toluene removal rate (%). Fig. 2 shows that the filters using the adsorbents of Examples 1 to 16 had a high toluene removal rate relative to the pressure loss, while the filters using the adsorbents of Comparative Examples 1 to 5 had a low toluene removal rate relative to the pressure loss.
[0077] As described above, the adsorbent of the present invention has a high toluene removal rate, and is capable of reducing the pressure loss when the adsorbent is used to prepare an adsorption filter.
[0078] <Example 17> Adsorbent A was silica gel (average particle length 600 μm, specific surface area 600 m 2 / g, pore volume 0.46 cm 3 / g, average pore size 24 Å) and powdered activated carbon (average particle length 15 μm, specific surface area 1000 m) as adsorbent B. 2 / g, pore volume 0.46 cm 3 / g, average pore size 17 Å) were mixed in a weight ratio of 7:1, and an aqueous solution of sodium alginate (ALG-Na) was added in an amount of 0.46 times the total weight of the silica gel and powdered activated carbon and mixed. The molecular weight of sodium alginate (ALG-Na) was 55,000, and the concentration of the aqueous solution of sodium alginate (ALG-Na) was 4.4% by weight. This was dried to obtain an adsorbent in which powdered activated carbon was fixed to the surface of the silica gel. An adsorption filter was also produced using the obtained adsorbent in the same manner as in Example 2. The manufacturing conditions and measurement results of the adsorbent are shown in Table 4.
[0079] <Comparative Example 6> Instead of granular activated carbon, silica gel (average particle diameter 600 μm, specific surface area 600 m 2 / g, pore volume 0.46 cm 3 Except for using an adsorbent of 1000 g / g and an average pore size of 24 Å, an adsorption filter was obtained in the same manner as in Comparative Example 2. The manufacturing conditions and measurement results of the adsorbent are shown in Table 4.
[0080] [Table 4]
[0081] FIG. 3 is a graph showing the relationship between the toluene removal rate and pressure loss when the adsorption filter is made using the adsorbent of Example 17, which uses silica gel as the adsorbent A, and the adsorbent of Comparative Example 6. The horizontal axis is pressure loss (mmaq), and the vertical axis is toluene removal rate (%). From Table 4 and FIG. 3, it can be seen that the filter using the adsorbent of Example 17 has a high toluene removal rate relative to the pressure loss, and the filter using the adsorbent of Comparative Example 6 has a low toluene removal rate relative to the pressure loss. From this, it can be seen that the effect of the present invention can be achieved by adsorbent B being fixed to the surface of adsorbent A, regardless of the type of adsorbent. [Industrial Applicability]
[0082] By using the adsorbent of the present invention, it is possible to remove pollutants including volatile organic compounds such as toluene and aldehydes efficiently with low pressure loss, which is expected to make a great contribution to the industrial world.
Claims
1. The adsorbent A has an average particle length of 200 μm to 1000 μm, and the adsorbent B has an average particle length of 0.1 μm to 100 μm, The adsorbent B is fixed to the surface of the adsorbent A, The number of the adsorbents B fixed to one particle of the adsorbent A is 500 or more.
2. The average particle length R of the adsorbent A A and the average particle major axis R of the adsorbent B B Ratio of R B / R A The adsorbent according to claim 1, wherein the ratio of the solubility of the adsorbent to the total solubility of the adsorbent is 1 / 5000 to 1 / 5.
3. The average particle length R of the adsorbent A A , the average particle major axis R of the adsorbent B B and the weight ratio P ((weight of adsorbent A) / (weight of adsorbent B)) of the adsorbent A and the adsorbent B is P=R A 3 / [{(R A +2R B ) 3 -R A 3 3. The adsorbent according to claim 1 or 2, which satisfies the relationship: x x, where x is 0.1 or more and 10 or less.
4. 3. The adsorbent according to claim 1, wherein the adsorbent A is any one of activated carbon, activated alumina, silica gel, and zeolite.
5. 3. The adsorbent according to claim 1, wherein the adsorbent B is any one of activated carbon, activated alumina, silica gel, and zeolite.
6. 3. The adsorbent according to claim 1, wherein the adsorbent B is fixed to the surface of the adsorbent A via a binder.
7. The adsorbent according to claim 6, wherein the binder is at least one selected from the group consisting of sodium alginate, polyvinyl alcohol, polyacrylamide, carboxymethyl cellulose, polyvinylpyrrolidone, polyacrylic acid, polymethacrylic acid, polystyrene sulfonic acid, polyethylene glycol, polypropylene glycol, polyvinyl acetate, and copolymers thereof.
Citation Information
Patent Citations
Filter medium
JP2015157250A
Cohesive activated carbon air filter
JP3612329B2